Longitudinal changes in outer nuclear layer thickness in soft drusen and reticular pseudodrusen. (18th March 2019) - Ramon, Clara; Cardona, Genis; Biarnés, Marc; Ferraro, Lucia L; Monés, Jordi
Abstract : Background: Drusen are seen in the early and intermediate stages of age‐related macular degeneration. A retrospective, two‐year observational study at a tertiary centre was designed to assess outer nuclear layer thickness in different types of drusen. Methods: Patients over 50 years of age with predominant soft drusen or reticular pseudodrusen were included in the study. Fundus photography, infrared, fundus autofluorescence and spectral domain optical coherence tomography were performed at baseline, years one and two. Outer nuclear layer thickness was measured in the nine Early Treatment Diabetic Retinopathy Study subfields, and the rate of thinning was determined using generalised estimating equations models. Results: Data were analysed from 17 eyes with soft drusen and nine eyes with reticular pseudodrusen. Greater outer nuclear layer thinning was seen overall and in all subfields in reticular pseudodrusen as compared to soft drusen, with statistically significant differences found mostly in superior and nasal subfields of ring 2. The outer nuclear layer was 5–12 μm thinner in eyes with reticular pseudodrusen, and the rate of thinning was greater in eyes with reticular pseudodrusen in the outer superior subfield. Conclusions: Outer nuclear layer thickness is consistently lower in patients with reticular pseudodrusen compared with soft drusen, irrespective of subfield location. These structural findings may contribute to explain the functional abnormalities observed in patients with reticular pseudodrusen.